Penile Corporeal Reconstruction during Difficult Placement of a Penile Prosthesis - Viet Q. Tran; Timothy F. Lesser; Dennis H. Kim; Sherif R. Aboseif (Advances in Urology)
For some patients with impotence and concomitant severe tunical/corporeal tissue fibrosis, insertion of a penile prosthesis is the only option to restore erectile function. Closing the tunica over an inflatable penile prosthesis in these patients can be challenging. We review our previous study which included 15 patients with severe corporeal or tunical fibrosis who underwent corporeal reconstruction with autologous rectus fascia to allow placement of an inflatable penile prosthesis. At a mean follow-up of 18 months (range 12 to 64), all patients had a prosthesis that was functioning properly without evidence of separation, herniation, or erosion of the graft. Sexual activity resumed at a mean time of 9 weeks (range 8 to 10). There were no adverse events related to the graft or its harvest. Use of rectus fascia graft for coverage of a tunical defect during a difficult penile prosthesis placement is surgically feasible, safe, and efficacious.